Sequential implantations of deuterium and helium ions into tungsten-coated composite structures - Azarenkov, N.A.; Bobkov, V.V.; Tishchenko, L.P.; Starovoitov, R.I.; Kovtunenko, Yu.I.; Logachev, Yu.E.; Gamayunova, L.A. (Вопросы атомной науки и техники, 2016)
The trapping and thermal desorption of deuterium and helium implanted into tungsten-coated composite structures were studied. The amount of accumulated deuterium and helium, and the shape of thermal desorption spectra were shown to be depended on the way of irradiation by the D⁺ and He⁺ ions: individually or sequentially. The possible mechanisms of these processes are proposed.